School engagement in three Senegalese secondary schools - Aoshika, Natsuki (2014)
The purpose of the research was to examine how is the construct and the prediction of school engagement and affective, cognitive and behavior engagement subdimensions in Senegalese secondary school. Another matter of interest was to find out what kind of the support experiences students get from teachers, family and peers. The cross-sectional data of research consisted of Senegalese junior high school students (N＝571, age10 – 20 years) from three schools located in Fatick province, Senegal. Participants answered self - report questionnaires in May 2013. The data was analyzed with factor analysis, reliability analysis with Cronbach alpha, t-test and One-way analysis of Variance (ANOVA) were used. Results also suggests that the Senegalese version of Student Engagement Instrument (SEI) has unique features which can not compare to Western model of SEI due to language issue, fragile education system and culture. However, the theory of School Engagement can be a useful concept of improving quality of education in Senegalese though understanding the student’ perception on schooling.